Pengaruh Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Bagian Produksi PT. Florindo Makmur - Andila, Dea; Halipah, Flora; Siregar, Aisyah (Management And Business Progress, 2024)
The aim of this research is to analyze and test the influence of training and work environment on employee performance with job satisfaction as an intervening variable in the production department of PT. Florindo Makmur. The population in this study were all employees of the production department of PT. Florindo Makmur, namely 35 people. Sampling was carried out using the Saturated Sample Technique. The data source in this research comes from primary data, namely from the results of questionnaires filled out directly by respondents. Hypothesis testing in this study used multiple linear regression analysis on the SPSS version 26.00 application. The analytical methods used are Instrument Test, Classical Assumption Test, Linear Regression Test, Determination Coefficient, Hypothesis Test and Sobel Test. The results of this research are that Training influences Employee Performance, Work Environment influences Employee Performance, Training influences Job Satisfaction, Work Environment influences Job Satisfaction, Job Satisfaction is unable to mediate the influence of Training on Employee Performance, and Job Satisfaction is able to mediate the influence between work environment and employee performance.